SOSIALISASI HARMONISASI PERATURAN PERPAJAKAN BAGI GURU-GURU SMA - Elmanizar, Elmanizar; Challen, Auliffi Ermian; Fitri, Hadiati (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2023)
The Law on Harmonization of Taxation Regulations covers the General Provisions and Procedures of Taxation, Income Tax, Value Added Tax, Taxpayer Voluntary Disclosure Program, Carbon Tax, and Excise. Because the Harmonization of Taxation Regulations contains new tax provisions (changes), teachers do not understand the contents of the Harmonization of Taxation Regulations. The purpose of this training on taxation is so that teachers can update their knowledge of the latest Tax regulations. So that the Economics subject material they teach will be updated, by Law No. 7 of 2021, namely Harmonization of Tax Regulations. The target of this training is economics teachers who are members of MGMP JP II. This training activity provides many benefits for teachers to increase the knowledge of Economics teachers in Taxation according to the latest regulations, namely Harmonization of Tax Regulations which at the same time becomes the uniformity of taxation material in Economics subjects in these various schools.